Public health aspects of low birth weight: Third report of the expert committee on maternal and child health - Expert committee on maternal and child health; World health organization (Geneva: Palais des nations, 1961)
WHO expert group on prematurity made a series of recommendations concerning programme planning in relation to the premature infant. It endorsed the international definition of prematurity (a birth weight of 2500 g or less) adopted by the first world health assembly in 1948.
Introduction -- Prerequisites for successful child-bearing -- Prematurity and low birth weight -- Meeting the problem of low birth weight -- The research programme
Keywords: Medical Science